The Future Counsellors: Challenges and Prospects in the Fourth Industrial Revolution - Balqis Olabisi Popoola; Olayemi Zainab Oduola; Yusuf Babatunde Kareem (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Background: The Fourth Industrial Revolution (4IR)—driven by artificial intelligence, robotics, big data and virtual platforms—is disrupting counselling in Nigeria, where youth unemployment, uneven infrastructure and legacy curricula constrain practice and employability. Aim: To identify the competencies, service models and policy levers required for Nigerian counsellors to remain effective and competitive in the 4IR. Method: A position-paper design using systematic document analysis of peer-reviewed articles, national and international policy reports, and labour-market statistics (2015–2025). The review followed a staged flow—scoping, eligibility screening, thematic categorisation and synthesis—using a document-analysis protocol and a coding matrix as instruments; data were analysed through thematic synthesis and integrative argumentation. Results and Discussion: Evidence indicates a persistent digital-skills gap in counsellor education (digital literacy, online/hybrid delivery, ethical data governance) and limited institutional readiness, which collectively depress service quality and labour-market outcomes. Yet, technology-enabled models—AI-assisted intake/triage, tele-mental-health platforms, secure cloud records and data-informed career guidance—can expand reach, reduce wait times, personalise interventions and strengthen counsellors’ roles in tackling youth employability and mental-health burdens. Realising these gains requires curriculum redesign aligned to 4IR competencies, mandatory CPD in cyberpsychology and data ethics, minimum technology standards and practice guidelines to manage privacy, bias and equity risks, with targeted support for rural and resource-constrained settings. Conclusion: The research answers its guiding question by showing that Nigerian counselling will sustain relevance only through a deliberate shift to technologically informed, ethically grounded hybrid practice, underwritten by curriculum reform, structured CPD and enabling policy and infrastructure; without this integration, counsellors face progressive marginalisation, whereas with it they can deliver broader access, higher efficiency and better outcomes.